Effect of parenteral trace element supplementation on oxidative stress and transcriptomic profile of peripheral blood in peripartum dairy cows - Calcaterra, Francisco (2024)
The transition period is the most critical period in the lactation cycle of dairy cattle. During this period, cows can be exposed to high oxidative stress (OS), which can be managed through mineral supplementation with antioxidant micronutrients. The aim of this study was to evaluate the gene expression profiles of transition dairy cows supplemented with the antioxidant trace elements copper (Cu), zinc (Zn), manganese (Mn) and selenium (Se). The study was conducted in a commercial Holstein dairy farm located in General Belgrano, Buenos Aires, Argentina. Cows (n = 12) were randomly assigned to either a supplemented or a control group (n = 6 each). Blood samples were obtained on the day of calving and 4, 7 and 14 days after calving. Superoxide dismutase and glutathione peroxidase activity, antioxidant capacity (AC), and thiobarbituric acid reactive substances were determined. With these data, OS index was calculated. Additionally, RNAsequencing analysis was performed on day +7, when OS index differences between groups were highest. The OS index and AC differed significantly between groups (day +7), despite only two differentially expressed genes codified for second messengers (p ≤ 0.05). This would suggest that trace mineral supplementation in transition dairy cows does not induce changes in the gene expression profiles of pathways associated with OS and immune function, whose expression is already high in response to the high OS levels and the dietary changes during this period. Nevertheless, supplementation with the studied minerals improved the pro-oxidant/ anti-oxidant balance.